MODERNIZATION OF TOURISM THROUGH THE PRISM OF THE BLUE ECONOMY AND SUSTAINABLE DEVELOPMENT (Development Service Industry Management, 2025)
The article explores the potential of the blue economy as a new paradigm for the sustainable development of coastal areas, focusing on the tourism sector.Today, the blue economy is a strategically important area of the sustainable economy that actively prevents climate change and supports protecting and preserving the marine environment. The European Union defines the blue economy as a key benchmark for long-term development with efficient and rational use of water resources. It was on the initiative of the European Union that Ukraine joined the Black Sea Blue Economy Fund initiative, which aims to combat pollution in the Black Sea and the coastal zone.The concept of the blue economy includes not only the study of the impact of climate and environmental aspects, but also includes industries associated with the traditional use of marine resources: marine and coastal tourism, fishing, water sports, transport, ports and logistics, and innovative areas (renewable offshore energy, aquaculture, marine biotechnology and bioprospecting, deep-sea mining).Tourism in the context of the blue economy covers various areas, including coastal, marine, ecological, and enogastronomic tourism. These types of tourism have great potential for creating jobs, developing infrastructure, attracting investment, and improving the living standards of local communities. Of particular importance coastal tourism, which includes beach holidays, cruises, diving, wildlife watching, and other activities that directly depend on the health of the marine and coastal ecosystems. It is also a powerful source of income, jobs, and investment. According to the World Bank, tourism in coastal regions provides livelihoods for millions of people, especially in countries with long coastlines.The key challenges and opportunities for integrating maritime and coastal tourism into sustainable economic growth strategies are considered. Tourism's role as a tool for preserving aquatic ecosystems, a source of employment, and social capital is outlined. International practices and prospects for Ukraine are analyzed.
Keywords: blue economy; sustainable development; coastal tourism; marine tourism; environmental management